2015
DOI: 10.1038/ncomms9143
|View full text |Cite
|
Sign up to set email alerts
|

A highly stable prefusion RSV F vaccine derived from structural analysis of the fusion mechanism

Abstract: Respiratory syncytial virus (RSV) causes acute lower respiratory tract infections and is the leading cause of infant hospitalizations. Recently, a promising vaccine antigen based on the RSV fusion protein (RSV F) stabilized in the native prefusion conformation has been described. Here we report alternative strategies to arrest RSV F in the prefusion conformation based on the prevention of hinge movements in the first refolding region and the elimination of proteolytic exposure of the fusion peptide. A limited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
348
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(362 citation statements)
references
References 35 publications
13
348
1
Order By: Relevance
“…Mab 13A8 possessed potency similar to that of motavizumab and D25. mAbs were tested for binding by ELISA to postfusion or prefusion-stabilized disulfide-cavity filling (DsCav1) or single chain-triple mutant (SC-TM) RSV strain A2 F proteins (17,18) and postfusion F from RSV strain 18537 B (Table 1 and Fig. S2).…”
Section: Resultsmentioning
confidence: 99%
“…Mab 13A8 possessed potency similar to that of motavizumab and D25. mAbs were tested for binding by ELISA to postfusion or prefusion-stabilized disulfide-cavity filling (DsCav1) or single chain-triple mutant (SC-TM) RSV strain A2 F proteins (17,18) and postfusion F from RSV strain 18537 B (Table 1 and Fig. S2).…”
Section: Resultsmentioning
confidence: 99%
“…Changes to the HRC (aa 75 to 97) region could be expected to affect processing as it is located N-terminal to the first cleavage site between amino acids 109 and 110. While there are currently no crystal structures of RSV F in its uncleaved state, it has previously been shown that the F protein is likely monomeric prior to cleavage and p27 removal (18,27). Changes in side chain packing may alter helical positioning within monomeric F, thereby affecting presentation of cleavage sites to the required protease(s).…”
Section: Discussionmentioning
confidence: 99%
“…This mutation was proposed to increase hydrophobic interactions between the loop, HRC, and part of HRA and effectively "stick" this loop to these domains. Another mutation at position 215 acted to reduce repulsion forces in this apex region where the HRA, HRD, and HRC helices meet (27).…”
Section: Discussionmentioning
confidence: 99%
“…46 Both of the F protein forms, particularly the pre-fusion form, induce potent neutralizing antibodies. [47][48][49] The identification and quantitative measurement of both the F protein forms were not investigated in this study because both forms induce powerful immune responses. However, we expect that a mixture of pre-and postfusion forms exist in the transfected cells, with the post-fusion form dominating due to its higher stability.…”
Section: Discussionmentioning
confidence: 99%